PROPERTY DEVELOPMENT: A BUSINESS PROCESS MODEL - Brink BOTHA; Christopher ADENDORFF; John SMALLWOOD (Journal of Construction Project Management and Innovation)
Property development constitutes one of the largest business enterprises and gross domestic product contributors of the world. The business of property development however incurred substantial losses over the centuries as a result of non-compliance to good governance in terms of considering all factors influencing perceived success of property development projects. The primary objective of this study was to develop a business process model for perceived success of property development projects, enterprises and role players. This model should guide role players, enterprises and actors within the property development business towards pro-active, effective and relevant decision making in achieving success in property development. To address the primary objective, a number of secondary objectives were raised whereby a conceptual model constituting identified variables was developed based on a comprehensive survey of the related literature. Appropriate hypotheses were formulated constructing a path diagram between the dependant variable and subsequent anteceding and intervening variables. Data was gathered using an electronic survey measuring primary data sourced from the identified international population of property development practitioners. This data was empirically analysed by means of structural equation modelling. The factors were namely financial risk forecast, consumer confidence and ability, procurement, urban planning, financial feasibility and practical viability considerations and professional feasibility and viability reporting, identified in the business process model affecting success of property development projects. This research broke new ground relative to the profession of property development in introducing the business process model for perceived success of property development.